Letter to the Editor of the Times Ventura County Edition from Jane Tolmach September, 2000 - Jane Tolmach:::::: (2000)
A letter from Jane Tolmach to the editor of the Times Ventura County Edition discussing the negative effects of the Oxnard Airport on the surrounding community.